Sosialisasi Situs Ulak Lebar Sebagai Warisan Sejarah Lokal pada Kelompok Musyawarah Guru Mata Pelajaran (MGMP) Sejarah Kota Lubuklinggau - Sarkowi Sarkowi; Agus Susilo; Ira Miyarni Sustianingsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Socialization of Ulak Lebar site at Lubuklinggau City Historical Teachers Forum aimed to provide detail information to historical teacher about historical sites at Lubuklinggau, South Sumatra. The existence of Ulak Lebar has not been utilized well yet by historical teachers at Lubuklinggau. That is why, the socialization was done to historical teachers forum in onder to have undestanding deeply about Ulak Lebar site. Finally, historical teching and learning process in the classroom use Ulak Lebar site as a historical learning source directly in field. So that Ulak Lebar site became a high valuable and meaningful to be one of interesting places for teacher and students. Besides, Ulak Lebar site became a valuable local related to historical, pedagogical, aesthetic and philosophical.